If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying P = 2(I + w) P = (I * 2 + w * 2) P = (2I + 2w) Solving P = 2I + 2w Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Simplifying P = 2I + 2w
| 6x+9=9-3x | | (50+-45x)+6=-6 | | 4r^2=4r-4 | | 3h-4k+7=3k-h | | m^2+3m=18 | | 2a^2=18a | | 5(10-9x)+6=6 | | 4(g+1)=2g-6 | | 12=4x-8 | | -12+48*67+4=x | | c-10c=0 | | 5r^2-43r+18=-6 | | 3x-3+2(2x)+13=-3-5x+(16-7) | | 2u^2-7u=4 | | -10c=0 | | 0.444w+6-0.333w=4 | | 2(x+1.1)=x+4.1 | | 2z^2+15x=0 | | 0.286y-0.833+0.714y=1.16 | | 3x+2[4-5(2x+1)]= | | y=8-2.5x | | 35=-3x^2-22x | | 5(t-2)=-10 | | 5+5y=55 | | 14-1.5x= | | -10(8n+-2)=60 | | -10(8n-2)=-60 | | -10=5(t-2) | | 9x-43=-30x-4 | | -10=5(-4-2) | | 4x-4+2(3x)+17=-3-3x+(16-7) | | 0=-16t^2+32t+12 |